PELATIHAN KETRAMPILAN STATISTIK DASAR DALAM AUDIT ENERGI RUMAH TANGGA PADA IBU-IBU PKK RT 03 SURODADI - Niken Retnowati; Septiana Wijayanti; Fery Firmansah; M. Wahid Syaifuddin; Tasari Tasari; Muhammad Ridlo Yuwono; Joko Sungkono; Yuliana Yuliana (WIDHARMA - Jurnal Pengabdian Widya Dharma, 2026)
Energy sustainability and its impact on climate change have become critical global and national priorities, with the household sector being a major contributor to electricity consumption. In the RT 03 Surodadi neightborhood, while there is a growing awareness of energy conservation among the PKK women (Family Welfare Movement), their efforts remain unmeasured and trial based. The primary challenge lies in the laack of technical skills to transform raw consumption data into actionable insights for identifying energy-intensive appliances. This community service project addresses this gap by providing training in basic statistics, including average calculations, percentages, and data visualization. By mastering these tools, participants will be able to independently conduct simple energy audits and develop data driven recomendation for household efficiency. Ultimately, this program aims to empower the women of RT 03 Surodadi to become analytical agents of change in promoting smartenergy conservation within their community.